Keggin Type‐Polyoxometalate Decorated Ruthenium Nanoparticles: Highly Active and Selective Nanocatalyst for the Oxidation of Veratryl Alcohol as a Lignin Model Compound. Issue 8 (14th March 2017) - Baguc, Ismail Burak; Saglam, Serif; Ertas, Ilknur Efecan; Keles, Muhammed Nuri; Celebi, Metin; Kaya, Murat; Zahmakiran, Mehmet
Abstract: Described herein is a new nanocatalyst system that efficiently works in the aerobic oxidation of veratryl alcohol (VA), which is formed by cleavage of β‐O‐4 linkages in lignin, to veratraldehyde (VAL) under mild reaction conditions. The new nanocatalyst system comprised of ruthenium(0) nanoparticles supported on the Keggin type polyoxometalate (POM; K3 [PMo12 O40 ]) network (Ru/POM) can simply and reproducibly be prepared by the dimethylamine‐borane ((CH3 )2 NHBH3 ) reduction of ruthenium(III) chloride trihydrate (RuCl3 .3H2 O) in isopropanol solution of K3 [P Mo12 O40 ] at room temperature. The characterization of Ru/POM by the combination of various analytical techniques reveals that the formation of well‐dispersed ruthenium(0) nanoparticles with a mean diameter of 4.7 ± 1.2 nm on the surface of POM network structure. This new Ru/POM nanocatalyst displays remarkable activity (TOF=7.5 mol VAld/mol Ru×h) at high selectivity (> 98%) and almost complete conversion (98%) in the aerobic oxidation of VA to VAld under mild conditions. Abstract : Ruthenium nanoparticles supported on polyoxometalate act as highly active and selective nanocatalyst for the aerobic oxidation of veratryl alcohol to veratraldehyde.